Pengaruh Pelatihan Kompetensi dan Motivasi Kerja terhadap Kinerja Guru SD Gugus Gajah Mada Muara Sugihan - Suprihatin Suprihatin; Syaiful Eddy; Reva Maria Valianti (CV. Ulil Albab Corp, 2026)
This study aims to identify and analyze: (1) the influence of competency training on teacher performance; (2) the influence of teachers’ work motivation on teacher performance; and (3) the simultaneous influence of competency training and teachers’ work motivation on teacher performance. This research is a quantitative study using a multiple correlation method. The study was conducted at the Gajah Mada Cluster Public Elementary Schools in Muara Sugihan District with 51 teacher respondents. Data collection techniques included questionnaires, observations, and documentation. Construct validity was used for the validity test, while reliability was tested using Cronbach’s Alpha. The prerequisite analysis tests consisted of normality, homogeneity, and linearity tests, and the data were analyzed using simple linear regression and multiple regression techniques. The results show that competency training and teachers’ work motivation, both individually and simultaneously, significantly influence teacher performance at the Gajah Mada Cluster Public Elementary Schools in Muara Sugihan District. The combined influence of competency training and teachers’ work motivation on teacher performance is 34.4%, while the remaining 65.6% is influenced by other variables not examined in this study.